1995
DOI: 10.1128/aac.39.12.2684
|View full text |Cite
|
Sign up to set email alerts
|

Intraphagocytic growth induces an antibiotic-resistant phenotype of Legionella pneumophila

Abstract: The antimicrobial susceptibilities of Legionella pneumophila isolates grown either in U937 human monocytic cells or in Acanthamoeba polyphaga were studied after release from the host cells without further subculture. Time-survival studies showed that exposure of L. pneumophila cells, grown exclusively in vitro, to 5 g of rifampin per ml resulted in at least 99.9% killing after 6 h and no detectable survivors at 24 h. Similar rates of killing were observed for in vitro-grown cells tested by exposure to ciproflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
118
0
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 39 publications
3
118
0
4
Order By: Relevance
“…RpoS has been implicated in the virulence of bacterial pathogens for animals (11) and protozoa (12). Legionella pneumophilus emerges after replication within Acanthamoeba both more virulent (13) and more resistant to chemical attack (14,15). It would thus seem that poly P has a role in the merged pathways of both virulence and resistance.…”
mentioning
confidence: 99%
“…RpoS has been implicated in the virulence of bacterial pathogens for animals (11) and protozoa (12). Legionella pneumophilus emerges after replication within Acanthamoeba both more virulent (13) and more resistant to chemical attack (14,15). It would thus seem that poly P has a role in the merged pathways of both virulence and resistance.…”
mentioning
confidence: 99%
“…Some of them, such as Legionella pneumophila, are even able to multiply within amoeba trophozoites (23,29) and could be found within amoeba cysts (14,27). Intracellular L. pneumophila is more resistant to biocides (3,4,14). Consequently, free-living amoebae, such as Acanthamoeba, have been recently described as important targets in water treatment (19,30).…”
mentioning
confidence: 99%
“…Therefore, it is very important to inhibit each stage of the L. pneumophila life cycle. In addition, Barker et al 1992 and1995 have reported that L. pneumophila grown in A. polyphage was less sensitive than L. pneumophila from cultures in broth to disinfectants and antibiotics because these bacteria undergo phenotype modifications upon intracellular growth.…”
Section: Discussionmentioning
confidence: 99%
“…in natural environments Greub and Raoult, 2004Molmeret et al, 2005Rowbotham, 1980Winiecka-Krusnell and Linder, 2001 . In addition, L. pneumophila co-cultured with amoeba is less sensitive to typical chlorine disinfectants Barker et al, 1992Dupuy et al, 2011García et al, 2007Kim et al, 2002 and L. pneumophila multiplied in amoebae possess greater resistance to disinfectants and antibacterial agents than L. pneumophila from cultures in broth Bandyopadhyay et al, 2004Barker et al, 1995 . L. pneumophila in biofilms is also resistant to stressful environmental conditions and the actions of antibacterial agents Cooper and Hanlon, 2010Kim et al, 2002Wright et al, 1991 .…”
Section: Discussionmentioning
confidence: 99%